Development of Sound Wave E-learning Material by Integrating Contextual Teaching with Smartphone to Improve Students Critical and Creative Thinking Skills - Lailatul Fauziah; Asrizal Asrizal* (Universitas Syiah Kuala, 2023)
Twenty first century skills are necessary for students to solve problems and be successful in learning. One of the core subjects of 21st century skills is learning and innovation skills. Learning and innovation skills include critical thinking and creative thinking skills. Problems found in the field show that students' critical and creative thinking skills are still low. The solution is to develop sound wave E-learning material by integrating contextual teaching with smartphones to improve students' critical and creative thinking skills. The purpose of this study was to determine the results of the needs analysis, the validity test, and the practicality test of the use of e-learning material. The research method used is the Hannafin and Peck development model which consists of needs analysis, design, and development and implementation. The research data were in the form of questionnaires, performance questions, validation and practicality instruments. Data analysis used a Likert scale, using Aiken's V formula to analyze the validity level and statistical analysis formulas to analyze the practicality of e-learning material. The results of the analysis showed that students' critical and creative thinking skills were still low. Then the developed e-learning material are valid with a value of 0.89 and the level of practicality is very good with a value of 86.52. Based on the research conducted, it can be concluded that the sound wave e-learning material by integrating contextual teaching with smartphone are valid and practical so that they can be used in the learning process